Combination of Doxorubicin and Areca Ethanolic Extract Induces Apoptosis by Increasing Caspase-3 Level on Breast Cancer (T47D) Cells - Rahmi, Fitria; Meiyanto, Edy; Susidarti, Ratna Asmah (Indonesian Research Gateway, 2012)
Despite causing many side effects, doxorubicin (Dox) is still one of breast cancer drug of choice. Thus, combination of chemotherapy is developed in order to decrease doxorubicin regimen dose. The aim of this research is to examine the combination effect of doxorubicin (dox) and areca extract (AE) on T47D human breast cancer cells. The cytotoxic activity was determined using MTT assay. The combination index (Cl) of the combination treatment was calculated to determine the effects (synergistic, additive or antagonistic). The combination application of dox (6-22nM) and AE (8-30Î¼g/ml) on T47D cells showed synergistic (Cl<0.9) or addictive effect )Cl =0.9-I.I). The effective combincation of dox-AE was 6nM-8Î¼g/ml on Cl<0.5. Apoptosis induction of AE solely and its combination with dox was the observed using double staining method. Moreover, expression of Bax and caspase-3 protein which mediated apoptosis, were observed using immunocytochemistry. Combination of AE and Dox increased expression of Caspase-3 but did not increase expression of Bax. This result showed AE increase the effectiveness of doxorubicin against T47D cells.Keyword : Breast cancer, doxorubicin, areca extract, T47D cells